RESPON BEBERAPA MEDIA PEMBIBITAN TERHADAP PERTUMBUHAN BIBIT ALPUKAT (Persea americana Miller.) - Bambang Kuswara; Nini Marta (Jurnal Agroekoteknologi, 2016)
Avocado plant nurseries often constrained by the type of planting medium used. The research objective was to determine the response of some types of media on the growth of seedlings of avocado. The research was conducted from September 2015 until January 2016 at the Aripan Experimental Garden, Indonesian Tropical Fruit Research Institute, Solok (West Sumatra). The design used in this experiment was a randomized block design with six treatments and four replications. The treatments given in these experiments were the soil, soil and manure 1: 1, soil and husks 1: 1, soil and husks 2: 1, soil and husk 3: 1, soil, husks and manure 1: 1: 1. The whole experiment consisted of 24 experimental unit and each experimental unit consisted of 10 plants. The results showed that the mix of soil and manure gives the best growth in avocado seedlings.Keywords: Avocados, Media, Manure